2014
DOI: 10.1038/srep03606
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Role of Catalysts in Carbon Nanotubes and Nanofibers by Scanning Transmission X-ray Microscopy

Abstract: The identification of effective components on the atomic scale in carbon nanomaterials which improve the performance in various applications remains outstanding challenges. Here the catalyst residues in individual carbon nanotube (CNT) and carbon nanofiber (CNF) were clearly imaged with a concurrent characterization of their electronic structure by nanoscale scanning transmission X-ray microscopy. Except for prominent catalyst nanoparticle at the tip, tiny catalyst clusters along the tube (fiber) were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 24 publications
2
30
0
1
Order By: Relevance
“…Catalyst residues may also contribute a lot to the performance of carbon nanomaterials . Recently, STXM experiments revealed the existence of catalyst residues in single CNT and carbon nanofiber (CNF) . The results showed that catalyst residues could be both prominent nanoparticles at the end of tube (or fiber) and tiny particles along the tube (or fiber), which was hard to be observed by normal image but could be clearly revealed by the elemental sensitive XANES spectra.…”
Section: Carbon Nanostructures In Energy Applicationssupporting
confidence: 70%
See 1 more Smart Citation
“…Catalyst residues may also contribute a lot to the performance of carbon nanomaterials . Recently, STXM experiments revealed the existence of catalyst residues in single CNT and carbon nanofiber (CNF) . The results showed that catalyst residues could be both prominent nanoparticles at the end of tube (or fiber) and tiny particles along the tube (or fiber), which was hard to be observed by normal image but could be clearly revealed by the elemental sensitive XANES spectra.…”
Section: Carbon Nanostructures In Energy Applicationssupporting
confidence: 70%
“…The results showed that catalyst residues could be both prominent nanoparticles at the end of tube (or fiber) and tiny particles along the tube (or fiber), which was hard to be observed by normal image but could be clearly revealed by the elemental sensitive XANES spectra. The existence of tiny particles suggested that catalysts might migrate in the growth process, which could contribute to various applications as observed in previous report for ORR . The STXM results also revealed the catalyst‐CNT (or CNF) interface interaction …”
Section: Carbon Nanostructures In Energy Applicationssupporting
confidence: 70%
“…58 Analogous to similar results reported in the literature for other metals, 59,60 the small component at 285 eV can be associated with a local rehybridization of G to sp 3 carbon, also driven by the strong Fe-C interaction. From the absence of C 1s peak components at ca 283.2 eV (Figure 2.b-f) and from the Fe L 2,3 XANES data (Figure 5.a,c), which indicate a zerovalent nature of Fe, 61 we can exclude the formation of iron carbides. A Volmer-Weber (VW) type 3D island growth of Fe NPs is observed in Fe/G/Pt(111) at very low coverage (~0.1 ML) and RT, with a preferential nucleation at G domain boundaries and point defects (Figure 6.a,b,c).…”
Section: In-situ Iron Deposition and Intercalationmentioning
confidence: 90%
“…Известно [2,3], что при синтезе УНТ методом CVD (chemical vapor deposition) в качестве катализатора роста часто применяются пере-ходные металлы (Fe, Co, Ni). При этом частицы катали-затора, встроенные в структуру УНТ, взаимодействуют со стенками нанотрубок и могут значительно влиять на электронную структуру и свойства нанотрубок.…”
Section: Introductionunclassified